Evaluation of Importance of Drain in Elective Abdominal Surgeries - Bhattacharjee, Anurag; Ramteke, Harshal (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND: Drains usage has been used in surgery for many years to prevent the accumulation of bodily fluids and improving body function.Objectives: To study the outcome in abdominal surgeries by comparing “drain” and “non-drain” group. METHODS-All the abdominal surgery cases of both sexes admitted in surgical ward through OPD basis requiring elective abdominal surgeries for various abdominal pathologies will be evaluated with detailed history. CONCLUSION-Drain use may lead to similar wound infections ,need for additional open procedures for postoperative complications and quality of life scores versus when compared with no drain use. RESULT-Use of prophylactic drain in abdominal surgeries shows no advantage in helping in reduction of postoperative complications or any other surgical benefit for the same.